THE ROMAN KINGS IN OROSIUS' HISTORIAE ADVERSVM PAGANOS*. (2nd November 2017) - Gassman, Mattias
Abstract : We are ruled by judges whom we know, we enjoy the benefits | Of peace and war, as if the warrior Quirinus, | As if peaceful Numa were governing (Claud. IV Cons. Hon. 491–3). With these words the poet Claudian lauds the Emperor Honorius on the occasion of his fourth consulship in 398 by comparing him to Rome's deified founder, Romulus-Quirinus, and to Numa Pompilius, its second king, who was proverbial for wisdom and piety. Claudian's panegyric stands in a long literary tradition in which the legendary Roman kings were depicted as models of statesmanship. This exemplary tradition left its mark on a broad array of late antique works, including historical compendia such as the pseudo-Aurelian De uiris illustribus, which narrates the kings' deeds as soldiers and statesmen, and the writings of antiquarians such as Macrobius and Servius, who collected information on the kings' invention of cults and calendars. Servius' interest in the kings implies that they featured in the teaching provided by other late antique grammatici as well, and thus that most literate Latin-speakers would have had some knowledge of their deeds. Advanced education in rhetoric likewise drew on Virgil and other school texts for historical exempla including Romulus and Numa, who appear in panegyrics and in brief histories, such as Eutropius' Breviary, that probably served as reference texts for the political elite. The kings thus loomed large in Roman perceptions of the founding of their empire, which began with the heroic Romulus, was strengthened by Numa's establishment of the Roman cultic system, and was secured by the later kings' political and military successes.